2012
DOI: 10.1136/annrheumdis-2012-201536
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre, blinded, randomised, placebo-controlled, laboratory-based study of MQX-503, a novel topical gel formulation of nitroglycerine, in patients with Raynaud phenomenon

Abstract: Treatment with MQX-503 caused a significant improvement in skin BF compared with placebo. Data from this proof of concept study suggest benefit of MQX-503 in subjects with RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…Topical GTN has previously been investigated as a ‘local’ treatment for RP (including SSc-related RP) and is currently being revisited (Hummers et al, 2013). In a small crossover study of topical GTN for secondary RP (mainly SSc), Franks (1982) observed there was a marked improvement in DUs with GTN, but not with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Topical GTN has previously been investigated as a ‘local’ treatment for RP (including SSc-related RP) and is currently being revisited (Hummers et al, 2013). In a small crossover study of topical GTN for secondary RP (mainly SSc), Franks (1982) observed there was a marked improvement in DUs with GTN, but not with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse side eff ects, such as headache, fl ushing, light-headedness, decreased blood pressure, tachycardia and aggravation of gastroesophageal refl ux, can occur. A novel formulation of topical NTG, i.e., MQX-503 gel, with fewer systemic side eff ects, has been assessed in two prospective studies, revealing benefi cial eff ects on the severity and duration of attacks and increased skin blood fl ow measured by laser Doppler techniques [44,47]. In patients with low blood pressure, acute or chronic heart failure, pulmonary hypertension, or concomitant use of a PDE inhibitor, topical nitrates should generally be avoided.…”
Section: Other Oral Vasodilatorsmentioning
confidence: 99%
“…V praksi se uporablja bosentan, ki je sintetični zaviralec obeh receptorjev. Pomembno zmanjša število novih razjed pri bolnikih s sekundarnim RF (29), tako da je EULAR priporočila uporabo zdravila, ko so simptomi, kljub zdravljenju s kalcijevimi antagonisti in prostaglandini, še vedno prisotni (34). Predvsem se uporablja za zdravljenje napredovalih oblik sekundarnega RF pri sistemski sklerozi (31).…”
Section: Antagonisti Endotelinskih Receptorjevunclassified